Hemodynamic changes in different types of carotid endarterectomy in the short- and long-term postoperative periods in patients with carotid artery stenosis - P. V. Ignatenko; A. A. Gostev; O. A. Novikova; Sh. B. Saaya; A. A. Rabtsun; I. V. Popova; A. V. Cheban; G. A. Zeidlitz; Yu. Е. Klevanets; V. B. Starodubtsev; A. А. Karpenko (Кардиоваскулярная терапия и профилактика)
Aim. To compare a novel technique of carotid endarterectomy (CEA) with autoarterial remodeling (AAR) of carotid bifurcation and the conventional patch angioplasty in relation to effect on 24-hour blood pressure (BP) and heart rate (HR) in the short- and long-term postoperative periods.Material and methods. This prospective, randomized, comparative trial included 200 patients which were divided into 2 groups: group 1 (n=100) — patients after CEA with AAR, group 2 (n=100) — patients after conventional xeno-pericardial patch repair. Twenty four-hour monitoring of BP and HR was performed before and after surgical treatment, both in short- and long-term postoperative periods in both groups. The follow-up period was 3 years.Results. Surgery in both groups was associated with an increase in HR, systolic and diastolic hypertension time index. Damage to carotid sinus enhances sympathetic innervation and disrupts the baroreflex regulation. Conclusion. The study did not reveal a significant difference in the incidence of postoperative hypertension and the dependence of HR on sel ected surgical technique. Thus, the proposed novel method of CEA with AAR of carotid bifurcation does not increase the risk of preexisting hypertension.